2020
DOI: 10.4103/tcmj.tcmj_131_19
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of laparoscopic hysteropexy and supracervical hysterectomy plus cervicopexy: A retrospective study

Abstract: Objectives: The objective of this study is to compare the outcomes of laparoscopic hysteropexy (LHP) and laparoscopic supracervical hysterectomy plus cervicopexy (LSHCP) for the treatment of pelvic organ prolapse (POP). Materials and Methods: We retrospectively included patients who had undergone laparoscopic sacral hysteropexy or hysterectomy plus cervicopexy between January 2015 and May 2019 at Hualien Tzu Chi Hospital, Taiwan. Age at surgery, body mass index (BMI) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…characterized by a longer follow up (60 months) compared with previous studies. 5,13,17 In the L-SCP group, the success rates for the apical, anterior, and posterior vaginal compartments were 100%, 95.5%, and 100%, respectively; whereas in the R-SHP group, the success rates were 97.8%, 93.5%, and 97.8% for the apical, anterior and posterior vaginal compartments, respectively. These results were not statistically different between the cohorts.…”
Section: Variables R-shp (Cases) L-scp (Controls) P-valuementioning
confidence: 99%
“…characterized by a longer follow up (60 months) compared with previous studies. 5,13,17 In the L-SCP group, the success rates for the apical, anterior, and posterior vaginal compartments were 100%, 95.5%, and 100%, respectively; whereas in the R-SHP group, the success rates were 97.8%, 93.5%, and 97.8% for the apical, anterior and posterior vaginal compartments, respectively. These results were not statistically different between the cohorts.…”
Section: Variables R-shp (Cases) L-scp (Controls) P-valuementioning
confidence: 99%
“…Twelve studies, two RCT 32,34 and 10 nRCS, 37,40,41,[45][46][47]51,52,56,65 reported information on the operative time for a total of 4461 pa- blood loss and methods used to assess it. Blood loss outcomes were reported in one RCT 34 and nine nRCS 37,40,41,[45][46][47]51,56,65 for a total of 4267 patients: 1764 hysterectomies and 2503 uterus-preserving procedures.…”
Section: Re Sultsmentioning
confidence: 99%
“…Twelve studies, two RCT 32,34 and 10 nRCS, 37,40,41,[45][46][47]51,52,56,65 reported information on the operative time for a total of 4461 pa- blood loss and methods used to assess it. Blood loss outcomes were reported in one RCT 34 and nine nRCS 37,40,41,[45][46][47]51,56,65 for a total of 4267 patients: 1764 hysterectomies and 2503 uterus-preserving procedures. In the pooled analysis, the intraoperative blood loss was lower in the uterine preservation group than in the hysterectomy group with a median difference of 61.7 mL (95% CI 31.3-92.1 mL; P < 0.001; I 2 = 97.39%) (Figures 6b and 7b).…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations